Biodegradable power sources for transient bioelectronics - Li Dong; Liangjie Shan; Yafei Wang; Ji Liu (Supramolecular Materials)
The development of biodegradable power sources has opened new avenues for transient bioelectronics, offering temporary energy solutions for implantable medical devices. This review presents a systematic overview on the design, materials, and functionalities of biodegradable devices for energy storage, harvesting, and transfer. Biodegradable batteries and supercapacitors provide reliable, short-term energy for implantable devices, while triboelectric and piezoelectric nanogenerators enable continuous energy harvesting from biomechanical sources. Additionally, wireless energy transfer systems enable safe power delivery without direct contact with biological tissues, broadening the scope of implantable bioelectronics. Future research should prioritize enhancing biocompatibility, increasing energy density, and refining degradation control to extend the practical applications of biodegradable power sources in bioelectronics.